Market-Driving Orientation (MDO) and the Survival of Manufacturing Small and Medium Enterprises in Nigeria - Nwankwo, Cosmas; MacDonald, Kanyangale (Acta Universitatis Danubius. Œconomica, 2022)
Small and medium enterprises (SMEs) are unlikely to change, shape or create markets if they are not careful to choose an appropriate market orientation. This positivistic study aims to examine the contribution of market-driving orientation to the survival of manufacturing SMEs in Nigeria by focusing on market sensing and alliance formation. The study used a quantitative research design and stratified random sampling to select owner-managers of manufacturing SMEs in Nigeria. Data were collected through a structured questionnaire administered to 364 owner-managers of SMEs. Exploratory and confirmatory factor analysis and structural equation modelling (SEM) were used to test the hypotheses with IBM SPSS-AMOS version 25. The results reveal that market sensing has a direct, strong and significant effect on the survival of manufacturing SMEs in Nigeria. In contrast, the effect of alliance formation is considered weak and insignificant to the survival of mature manufacturing SMEs. The study concludes that the focus on the overt needs of customers by mature manufacturing SMEs is necessary but inadequate without proactive market sensing of the latent needs of customers to ensure survival in the competitive market. Future research should re-examine the concept of alliance formation by focusing on SMEs in the nascent and growth stages of the organisational life cycle and adopt a more nuanced view of social capital to explore how collaborative processes create, maintain, and redefine alliances which drive rather than react to the market.